Policy mechanisms and spatial dynamics of low-carbon city construction in promoting inclusive green growth in China - Mu, Xuan; Zou, Tong (Frontiers in Environmental Science, 2025)
Against the backdrop of global climate governance and China’s dual-carbon goals, low-carbon city construction has emerged as a critical strategy for balancing economic growth and environmental sustainability. This study evaluates the impact of low-carbon city construction on inclusive green growth in China from 2006 to 2021. Empirical results indicate that these policies contribute to an average increase of 0.005 units in inclusive green growth for the treatment group compared to the control group, with robustness assessed through placebo tests and alternative variable substitutions. Further analysis indicates that the policy effects are more pronounced in central cities, resource-based cities, and cities with high carbon abatement potential, driven strongly by urban technological innovation, industrial structure optimization, and enhanced government leadership. However, spatial effect analysis shows that, despite a significant positive spatial correlation between cities, the spillover effects of low-carbon policies are limited, primarily concentrated within the pilot cities. Therefore, it is recommended to strengthen cross-regional governance alliances, establish green technology transfer centers, promote the “R&D-manufacturing-recycling” industrial chain, and deploy tailored regional transformation incentives. Additionally, drawing on international models such as the EU’s carbon border mechanism and Germany’s industry-university-research framework, collaborative “regional green growth partnerships” should be developed to foster inclusive green growth.